2022
DOI: 10.3390/ijms23010497
|View full text |Cite
|
Sign up to set email alerts
|

MTEP, a Selective mGluR5 Antagonist, Had a Neuroprotective Effect but Did Not Prevent the Development of Spontaneous Recurrent Seizures and Behavioral Comorbidities in the Rat Lithium–Pilocarpine Model of Epilepsy

Abstract: Metabotropic glutamate receptors (mGluRs) are expressed predominantly on neurons and glial cells and are involved in the modulation of a wide range of signal transduction cascades. Therefore, different subtypes of mGluRs are considered a promising target for the treatment of various brain diseases. Previous studies have demonstrated the seizure-induced upregulation of mGluR5; however, its functional significance is still unclear. In the present study, we aimed to clarify the effect of treatment with the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 107 publications
(125 reference statements)
3
4
0
Order By: Relevance
“…As a result of these data, epilepsy can be induced by a disruption in GABAergic and glutamatergic neurotransmission. These findings are consistent with earlier findings [ 1 , 9 , 13 , 16 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As a result of these data, epilepsy can be induced by a disruption in GABAergic and glutamatergic neurotransmission. These findings are consistent with earlier findings [ 1 , 9 , 13 , 16 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…Glutamate hyperactivation of NMDARs promotes neuronal excitotoxicity and degeneration via many pathways, including nitric oxide synthase activation, ROS, and RNS production [ 37 ]. The pathophysiology of pilocarpine-induced epilepsy is considered to include both oxidative and nitrosative stress, as persistent seizures cause an increase in mitochondrial oxidative and nitrosative stress, with subsequent cell damage [ 13 , 29 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPEP and MTEP, antagonists of group I mGluRs, provided a neuroprotective effect in models of epilepsy [ 42 , 43 ]. A study performed in our laboratory also showed the neuroprotective effect of MTEP, but administration of this antagonist did not prevent the development of epilepsy [ 44 ]. Simultaneously, activation of mGluR5 provided functional recovery after brain injury and reduced neuroinflammation in virus-induced epilepsy [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the RNA was precipitated with LiCl. RNA concentration and purity were determined as described previously [ 44 ].…”
Section: Methodsmentioning
confidence: 99%